Acute fatigue in indoor court-based team sports: A systematic review - Anthony Clark; Omar Heyward; Lara Paul; Ben Jones; Sarah Whitehead (PLoS ONE, 2025)
Fatigue in team sports has been widely researched, with a number of systematic reviews summarising the acute (i.e., within 48-hours) response in outdoor sports. However, the fatigue response to indoor court-based sports is likely to differ to outdoor sports due to smaller playing fields, harder surfaces, and greater match frequencies, thus should be considered separately to outdoor sports. Therefore, this study aimed to conduct a systematic review on acute fatigue in indoor court-based team-sport, identify methods and markers used to measure acute fatigue, and describe acute fatigue responses. A systematic search of the electronic databases (PubMed, SPORTDiscus, MEDLINE and CINHAL) was conducted from earliest record to June 2023. Included studies investigated either a physical, technical, perceptual, or physiological response taken before and after training, match, or tournament play. One-hundred and eight studies were included, measuring 142 markers of fatigue. Large variability in methods, fatigue markers and timeline of measurements were present. Cortisol (n =  43), creatine kinase (n =  28), countermovement jump (n =  26) and testosterone (n =  23) were the most frequently examined fatigue markers. Creatine kinase displayed the most consistent trend, increasing 10–204% at 24-hours across sports. There is large variability across studies in the methods and markers used to determine acute fatigue responses in indoor court-based team sports. Future researchers should focus on markers that display high reliability and transfer to practice. The robustness of studies may be increased by ensuring appropriate methods and timescale of fatigue marker measurement are used. Further research is required to determine which combination of markers best describes a fatigue response.